Finger-to-Beat Coordination Skill of Non-dancers, Street Dancers, and the World Champion of a Street-Dance Competition - Miura, Akito; Fujii, Shinya; Okano, Masahiro; Kudo, Kazutoshi; Nakazawa, Kimitaka (Frontiers in Psychology, 2016)
The coordination of body movements to a musical beat is a common feature of many dance styles. However, the auditory–motor coordination skills of dancers remain largely uninvestigated. The purpose of this study was to examine the auditory–motor coordination skills of non-dancers, street dancers, and the winner of a celebrated international street dance competition, while coordinating their rhythmic finger movements to a beat. The beat rate of a metronome increased from 1.0 to 3.7 Hz. The participants were asked to either flex or extend their index fingers on the beat in each condition. Under the extend-on-the-beat condition, both the dancers and non-dancers showed a spontaneous transition from the extend-on-the-beat to the flex-on-the-beat or to a phase wandering pattern. However, the critical frequency at which the transition occurred was significantly higher in the dancers (3.3 Hz) than in the non-dancers (2.6 Hz). Under the flex-on-the-beat condition, the dancers were able to maintain their coordination pattern more stably at high beat rates compared to the non-dancers. Furthermore, the world champion matched the timing of movement peak velocity to the beat across the different beat rates. This may give a sense of unity between the movement and the beat for the audience because the peak velocity of the rhythmic movement works as a temporal cue for the audiovisual synchrony perception. These results suggest that the skills of accomplished dancers lie in their small finger movements and that the sensorimotor learning of street dance is characterized by a stabilization of the coordination patterns, including the inhibition of an unintentional transition to other coordination patterns.